2017
DOI: 10.1186/s12957-017-1195-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation of sentinel lymphatic channels (SLCs) and sentinel lymph nodes (SLNs) assessed by contrast-enhanced ultrasound (CEUS) in breast cancer patients

Abstract: BackgroundThe objective of this study was to assess the feasibility of detecting the variation of sentinel lymphatic channels (SLCs) and sentinel lymph nodes (SLNs) in breast cancer patients using contrast-enhanced ultrasound (CEUS).MethodsA total of 46 breast cancer patients were prospectively recruited in the study. All the participants received intradermal and peritumoral injection of microbubbles as contrast agent, and SLCs and SLNs were assessed preoperatively. Blue dye was injected subareolarly and perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…Of 567 studies identified from the initial search, 35 cohort studies (4244 subjects) satisfied the inclusion and exclusion criteria, and were included in this meta‐analysis (Fig . , Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 567 studies identified from the initial search, 35 cohort studies (4244 subjects) satisfied the inclusion and exclusion criteria, and were included in this meta‐analysis (Fig . , Table ).…”
Section: Resultsmentioning
confidence: 99%
“…, Table ). Among the studies included, 22 15,16,20–23,26,27,30–32,34,35,38–41,43–45,47,49 reported on the performance of ICG, eight on SPIO and five on CEUS. The mean age of included subjects was 57 years.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed that CEUS can further improve identification of SLN and reduce SLNB surgical trauma [23][24][25][26]. However, some studies suggested that the false negative rate of SLNB guided by CEUS alone is high and the diagnostic accuracy is low [27,28]. Since the difference in accuracy of assessing axillary status between CEUS-guided SLNB and conventional SLNB is not clear, this meta-analysis reviews the reported studies focusing on SLNB guided by CEUS, further analyzes the difference in the positive rate between SLNs identified by CEUS and SLNs identified not by CEUS, and also analyzes the accuracy of SLN identified by CEUS in diagnosing the pathological status of overall axillary sentinel nodes, in order to explore whether CEUS can further improve the accuracy of sentinel lymph node biopsy.…”
Section: Ultrasonography and Contrast-enhanced Ultrasoundmentioning
confidence: 99%
“…Of the 16 selected studies, 9 used SonoVue as CEUS material [26][27][28][39][40][41][42][43][44], 6 used Sonazoid [23][24][25][45][46][47], and 1 used DEFINITY [48]. The administration sites and methods of contrast agents mainly include intradermal [23-28, 39-44, 47] and subcutaneous [45,46] injection around areola or peritumoral parenchyma injection approaching the axilla [48].…”
Section: The Localization Detection Rate Of Ceus For Slnmentioning
confidence: 99%
See 1 more Smart Citation